Preparation and characterization of cellulose acetate propionate membrane - Maryudi Maryudi; Dhias Cahya Hakika; Firda Mahira Alfiata Chusna; Amillia Amillia (Institute of Advanced Engineering and Science, 2024)
Membrane technology is a technique in water and wastewater treatment that has many advantages. This study focuses on the manufacture and characterization of cellulose acetate propionate (CAP) membranes using the phase inversion method. The CAP is preferable since it is a biopolymer that is environmentally friendly and cheap. The production of CAP membrane was carried out using phase inversion method, and varied in 3 different concentrations of CAP i.e., 13, 14, and 15% wt., with additional material of polyethylene glycol (PEG). The characterization was conducted using scanning electron microscopy (SEM) and Fourier transform infrared (FTIR) analysis to determine its morphology, pores, and functional groups. The results show that the membrane containing 13% wt. CAP exhibits higher porosity with more macropores than a membrane with 14 and 15% wt. CAP. However, membranes with higher concentrations of CAP show more uniform pores and fewer macropores. FTIR analysis confirmed the presence of functional groups in the membrane such as C-O, -CH3, C=O, C-H, and –OH. It is also found that there is a shift in Wavenumber due to the increase in the concentration of CAP in each membrane.